Zakat dan Transformasi Digital: Tantangan dan Peluang Pengelolaan Zakat Era Modern Berdasarkan Perspektif Hukum Syariah - Sujantoko, Gatot; Nashirudin, Muh.; Sabig, Fairuz (Universitas Muhammadiyah Makassar, 2024)
Digital transformation has an impact on various aspects of human life, including the way humans connect with God and fulfill their responsibilities as servants. For example, digital transformation is also bringing changes to conventional zakat mechanisms towards zakat that is integrated with internet and digital technology. This research aimed to explore the mechanism of zakat in the digital transformation era, the opportunities that arise, and the challenges that must be faced. This study used a qualitative approach, with data obtained from various literature studies. The results of the study showed that digital zakat has a unique mechanism that distinguishes it from conventional zakat management, including: 1) efficiency of the target selection system; 2) accessibility and convenience; 3) transparency and accountability; 4) efficient distribution and scale expansion; 5) ethical considerations; 6) individual interactivity and community involvement. In addition to individual interactivity and community involvement, the entire mechanism has complied with and is in accordance with Islamic law. Opportunities from the implementation of digital zakat are related to efficiency, the broader impact of zakat, and increased awareness and compliance of zakat payers. However, there are also challenges that must be faced related to institutional challenges, interpersonal challenges, security and privacy challenges, and regulatory challenges.Islamic law; digital transformation; digital zakat; zakat management.